Ilhan resources sdn bhd / Nur Farhana Abdul Samat ...[et al.] - Abdul Samat, Nur Farhana; Abd Rahman, Rosenah; Shamsudin, Shahida; Che Mohamed Sukri, Siti Nafisah; Abdul Gani, Siti Norfahana (2018)
llhan Resources Sdn Bhd is a company in manufacturing industry. This product is focusing in producing the Smart Medication Vest with technology based consists of sensors that are able to detect sounds and touch .The factory is located in Kuala Lumpur and our target marketing will be based at both government and private hospitals in Kuala Lumpur area. The product is made of 100% polyester and provided in pink, red, orange, and purple bright colors to easily catch everybody's eyes. The price of this Medication Safety Vest is very reasonable and value for money. The management team of our company consists of experienced and knowledgeable employees to guarantee a high quality products produced.